Microplastics in water, sediment and salts from traditional salt producing ponds - A. Tahir; P. Taba; M.F. Samawi; S. Werorilangi (Global Journal of Environmental Science and Management)
Plastic pollution has universally known accumulated in all environment compartments and accelerating threat to the sustainability of earth. Field survey to examine the occurrence of microplastics in ancient sea water evaporation technology of ponds at Pallengu-Jeneponto, was conducted. From this sea salt producing ponds, samples of water, sediment and freshly harvested salts were collected. Sixteen samples each of water and sediments and 12 salts were collected. From 16 water and sediment samples there are 31 microplastics item discovered in 11 water samples (68.75% of total contamination) and 41 microplastics item observed in 10 sediment samples (62.5% total contamination), respectively. Interestingly, sampling points at sedimentation/heating pools were found to be the locations with highest occurrence of microplastics in both water and sediment. There are 7 salt  samples positively contaminated with 29 microplastics or 58.3% of total contamination, which predominated by line and fragment forms. Fourier transform infra-red spectroscopy analysis has revealed polymers of polyvinyl acetate (41.7%), polyethylene (33.3%) and polystyrene (25%). There was no significant difference found on microplasticss occurrence from 3 kinds of samples collected, although there was a decreasing trend of total microplastics found from water, sediment and salt. Microplasticss abundance were ranged 7-55 items/L water, 14.6-50 items/kg sediments and 6.7-53.3 items/kg salt. With microplastics abundance reached over 53 microplastics items/kg salt, it is believed that continuous consumption by people will end up with possible accumulation of potentially absorbed of various toxic chemical pollutants which present in sea water as salt raw materials. The need for robust and practical strategy in water quality management for reduction of microplasticss contamination in consumed salts is a must.